LINC00662 sponges miR-107 accelerating the invasiveness and proliferation of glioma cells - Wu, Jinsong (J Cancer, 2020)
Increasing evidence revealed that the aberrant expression of long non-coding RNAs (lncRNAs) has been implicated in tumorigenesis. However, the role and mechanisms of LINC00662 in glioma have not been elucidated. Here, we show that upregulation of LINC00662 expression in glioma is associated with advanced clinical features and poor prognosis. Our results from loss-of-function assays suggest that LINC00662 silencing suppresses the proliferative and invasive abilities of glioma cells. In vivo, glioma growth was inhibited by depletion of LINC00662 in nude mice. Mechanistically, LINC00662 directly interacts with miR-107. The High-mobility group box 1 protein (HMGB1) is a known target of miR-107. Moreover, rescue assays reveal that HMGB1 overexpression (or miR-107 inhibition) reverses the glioma growth inhibition caused by LINC00662 knockdown. In conclusion, our results indicate that LINC00662 acts as an oncogene in glioma by modulating the miR-107/HMGB1 axis, suggesting that LINC00662 could be a novel therapeutic target for glioma treatment.